Evaluation of toxic heavy metal content in marketed Ayurvedic decoctions using closed vessel microwave digestion in ICPMS - Deepu Mohanan; Rammanohar Puthiyedath Nandakumar G
The heavy metal toxicity of marketed Ayurvedic herbal formulations has been sporadically reported in the literature. Drakshadi (DK) and Gandharvahastadi (GK) decoctions are widely prescribed classical Ayurvedic herbal formulations. The potential adverse heavy metal toxicity due to consequent intake of DK and GK have been published in scientific papers or reported through pharmacovigilance. The objective of our investigation was to determine the presence of heavy metals in marketed DK and GK, with reference to the Ayurveda Pharmacopeia of India (API) standards. In this study, the concentration of four heavy metals, Arsenic (As), Cadmium (Cd), Lead (Pb), and Mercury (Hg) were investigated using Inductively Coupled Plasma- Mass Spectrometer (ICP-MS). These metals are not known to have any role in the pharmacological activity of these formulations. However, their presence beyond acceptable limits can have harmful consequences. Eighteen random samples each of DK and GK decoctions were collected from different pharmacy outlets, Kerala province, India. We tested 36 market samples of the above formulations for heavy metals, which were found to be within the limits prescribed by the Ayurvedic Pharmacopoeia of India. Our study suggests that heavy metal contamination of Ayurvedic formulations may not be widespread as suspected. However, continuous dynamic monitoring of Ayurvedic herbal formulations for heavy metal contamination is warranted considering the possibility of inadvertent contamination of raw drugs from environmental exposure.